Average Vector Field Method of The Strongly Coupled Nonlinear Schrodinger Equation - akkoyunlu, canan (My University, 2019)
In this work, average vector field method (AVF) is derived for strongly coupled Schrodinger equation (SCNLS). The SCNLS equation is discretized in space by finite differences and is solved in time by structure preserving AVF method. Numerical results for different paremeter compare with the Lobatto IIIA-IIIB method.The results indicate that AVF method are effective to preserve global energy and momentum.